2013
DOI: 10.1007/s10509-013-1424-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of center of mass energy by particles collision in some black holes

Abstract: This paper is devoted to the study of particles collision for two well-known black holes. We consider particles moving in equatorial plane and calculate their center of mass energy. Firstly, we explore center of mass energy of a regular black hole. In this case, acceleration and collision of particles lead to high center of mass energy which is independent of event horizon and naked singularity. Secondly, we investigate the center of mass energy of Plebanski and Demianski black hole (non-extremal) with zero NU… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In the vicinity of extremal Kerr black hole, they have found that infinite centerof-mass energy (CME) can be achieved during the collision of particles. The BSW effect has been studied for different black hole spacetimes [18][19][20][21][22][23][24][25][26][27][28][29][30]. In this paper we obtain the CME expression for the colliding particles near horizon of Schwarzschild-like black hole surrounded by quintessence matter and BSW effect is studied for both neutral and charged particles.…”
Section: Introductionmentioning
confidence: 99%
“…In the vicinity of extremal Kerr black hole, they have found that infinite centerof-mass energy (CME) can be achieved during the collision of particles. The BSW effect has been studied for different black hole spacetimes [18][19][20][21][22][23][24][25][26][27][28][29][30]. In this paper we obtain the CME expression for the colliding particles near horizon of Schwarzschild-like black hole surrounded by quintessence matter and BSW effect is studied for both neutral and charged particles.…”
Section: Introductionmentioning
confidence: 99%
“…Further, if the collision occurs in the equatorial plane, the CME (3.25) at the horizon of the extremal KNTN black hole reduces to 31) which is indeed finite for all values of L 1 and L 2 except when L 1 or L 2 approaches the critical angular momentum, for which the CME is arbitrarily high. When the electric charge Q vanishes, eq.…”
Section: Near-horizon Collision Of Particles Around the Extremal Kntnmentioning
confidence: 96%
“…The CME of the collision for charged particles in a Bardeen black hole was studied in [30]. In [31], the authors investigated the CME near the horizon of a non-extremal Plebanski-Demianski black hole without NUT parameter. The CME in the background of Ayòn-Beato-Garcìa-Bronnikov (ABGB), Einstein-Maxwell-dilaton-axion (EMDA) and Bañados-Teitelboim-Zanelli (BTZ) black holes was investigated in [32].…”
Section: Jhep05(2015)147mentioning
confidence: 99%
“…In [5], it was shown that nonrotating but extremely charged black holes also cause similar divergences of the collision energy for critically charged particles. Many authors have discussed the BSW effect in a variety of situations [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34] and the possibilities of other processes of unboundedly high-energy collision, [35,36,37], and for a review see [38].…”
Section: Introductionmentioning
confidence: 99%